2022
DOI: 10.3389/fphar.2022.971849
|View full text |Cite
|
Sign up to set email alerts
|

Function-Wise Dual-Omics analysis for radiation pneumonitis prediction in lung cancer patients

Abstract: Purpose: This study investigates the impact of lung function on radiation pneumonitis prediction using a dual-omics analysis method.Methods: We retrospectively collected data of 126 stage III lung cancer patients treated with chemo-radiotherapy using intensity-modulated radiotherapy, including pre-treatment planning CT images, radiotherapy dose distribution, and contours of organs and structures. Lung perfusion functional images were generated using a previously developed deep learning method. The whole lung (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Based on these VOIs, radiomics and dose features were calculated from CT images and dose maps, respectively. More details on these two types of features have been documented in the current body of literature (Lam et al 2021 ; Li et al 2022a , b , c ; Zheng et al 2023 ).
Fig.
…”
Section: Methodsmentioning
confidence: 90%
“…Based on these VOIs, radiomics and dose features were calculated from CT images and dose maps, respectively. More details on these two types of features have been documented in the current body of literature (Lam et al 2021 ; Li et al 2022a , b , c ; Zheng et al 2023 ).
Fig.
…”
Section: Methodsmentioning
confidence: 90%
“…In a specific group of 126 stage III lung cancer patients treated with radio–chemotherapy, Li et al demonstrated that dual-omics features from different lung functional regions can improve the prediction of radiation pneumonitis [ 119 ]. Yoo et al assessed a machine learning model that was able to predict pathological complete response after treatment with neoadjuvant chemoradiotherapy by analyzing the texture features from pre- and post-treatment PET-CT studies of patients with stage III non-small-cell lung cancer [ 120 ].…”
Section: Future Perspectives Offered By Imagingmentioning
confidence: 99%
“…Based on these VOIs, radiomics and dose features were calculated from CT images and dose maps, respectively. More details on these two types of features have been documented in the current body of literature [29][30][31][32][33].…”
Section: Features Extractionmentioning
confidence: 99%